GERAKAN LITERASI MEMBACA (GERLICA) UNTUK MENINGKATKAN MINAT BACA MURID SD NEGERI GRAJEGAN 02 - Alri Anita Fatmawati (Jurnal Pustaka Cendekia Pendidikan, 2025)
Improving the quality of literacy is the key to building an intelligent and critical society. This study explores various approaches to improving the quality of literacy in education. By integrating innovative teaching methods, and relevant curriculum development, this study identifies factors that contribute to improving reading and writing skills. In addition, parental and community involvement in the learning process has proven effective in creating a supportive literacy environment. The results show that collaborative efforts between schools, families, and communities can result in significant improvements in the quality of literacy, preparing future generations to face complex information challenges. In the program that I created for this change initiative is the Reading Literacy Movement which I abbreviated to ‘’GERLICA’’ so that the title is interesting for students and attracts their attention. I prioritize this because students in my school have very low interest in reading and with many factors. Among them are the lack of reading books in the library, reading books are old and outdated. Teachers who are less innovative in carrying out learning activities, especially about literacy. Lack of cooperation with external parties, especially those related to literacy activities, for example with the regional library and so on. Lack of parental involvement in accompanying children, especially when learning activities at home. For that, with the program "GERLICA" Reading Literacy Movement to increase students' interest in learning, especially in the field of literacy. As well as improving innovative teacher learning. In addition, cooperation is established with external parties including Perpusda (Regional Library), CT Arsa Fondation.